Гроза: драма в пяти действиях / А. Н. Островский - Островский Александр Николаевич (Логосвос, 2014)
Экземпляры: БС (20170206) / Инвентарный номер: РТШ53911 / Сис.шифр: Р1 / Авт.знак: О-77 / ГРНТИ: 17 / ББК: 84(2)